A Process to Design Program Outcomes for Healthcare Education: Making Sense out of the Alphabet Soup - Hugh Stoddard; Erica Brownfield; Gordon Churchward; J. William Eley (Association of American Medical Colleges, 2015)
Abstract In recent years, educators have been experimenting with outcomes-based education programs to supplant the traditional time-based model. This resource presents the process used at Emory University School of Medicine (EUSOM) to locally create a student outcomes framework that would: (1) express the school's mission and guide its curriculum, (2) provide a basis for assessments through all years of the MD program, and (3) be consistent with national trends in healthcare education, particularly regarding the use of entrustable professional activities and the use of the Physician Competency Reference Set. The Instructor's Guide describes the process of developing program outcomes. Three exhibits to supplement the described process are also provided. The documents showing student physician activities (SPAs). These outcomes developed using this process are listed in two formats: (1) a parsimonious list of the SPAs with reference to a national framework, and (2) an explanatory list of SPAs with annotations and cross-references to other SPAs. The SPAs that were developed using the process described in this resource have been in use at EUSOM of Medicine since December 2013. Although one medical school's outcomes may not translate exactly to another school's unique mission and values, writing outcomes for education programs, along with the collaborative process that EUSOM used for adopting and implementing their SPAs, can readily be adopted by other programs.